Audience Responses to Advertisements Using Artificial Intelligence: A Case Study on Film Promotion - Ana Rimbasari; Agniya Thahira; Amalina Nur Arifah (Contemporary Journal on Business and Accounting, 2026)
Purpose – This study examines audience responses to advertisements utilizing artificial intelligence (AI) in film promotion campaigns conducted via social media platforms. The advertisements employ AI technology to create interactive content for promotional purposes. Design/methodology/approach – The research adopts a qualitative descriptive approach through a case study method, data were gathered via in-depth interviews and analyzed using triangulation techniques. Findings – The findings indicate that the majority of audiences responded positively, perceiving the advertisements as innovative, engaging, and relevant to contemporary issues. AI-driven advertisements were considered effective in clearly conveying the intended message. However, some audiences faced difficulties in understanding the technical aspects of AI, with certain individuals unaware of its application in the advertisements. The campaign successfully enhanced audience engagement and reinforced the brand’s image as an innovative entity. Originality – This study offers insights into the effectiveness of AI in marketing communication strategies within the entertainment industry.